Beyond Childhood Comfort: Dolls as Transitional Objects in Adaptive Emotion Regulation in Early Adulthood - Ceziasynita Guneralmedwal Jonas; Rulita Hendriyani (Journal of Educational, Health and Community Psychology, 2026)
This study aimed to explore the meaning of transitional object use and its role in emotion regulation in early adulthood. Two participants were selected through purposive sampling and were interviewed in depth across three sessions. The findings showed that beloved dolls functioned as stable attachment figures by providing a consistent sense of security and comfort, especially when human attachment figures were not consistently available. As they grew older, both participants interpreted the doll not only as a physical object but also as a tool for managing emotions through actions such as hugging, holding, twisting, and sniffing. A difference emerged in their level of dependence: R used the doll primarily during negative emotional states, whereas A used it across all emotional conditions, including positive ones. This study offers insight into the use of transitional objects in positive emotions and highlights their adaptive role when not used excessively.